2013
DOI: 10.1016/j.drugpo.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Methadone treatment improves tuberculosis treatment among hospitalized opioid dependent patients in Ukraine

Abstract: Background Ukraine’s volatile syndemics of tuberculosis (TB) and HIV among people who inject drugs (PWIDs) introduces numerous treatment challenges for each condition, including high mortality and development of multi-drug resistant TB (MDR-TB). Methods A prospective, non-randomized 90-day observational study was conducted in six Ukrainian TB treatment sites to assess the effectiveness of integrating methadone maintenance (MMT) with TB treatment using: (1) 90-day TB treatment retention; (2) time to treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Irrespective of etiology, the healthcare reform should shift to more integrated care settings (Bachireddy et al, 2014; Sylla, Bruce, Kamarulzaman, & Altice, 2007) that incorporate treatment for HIV, TB and opioid dependence, including in hospitalized settings. Important in our findings is that none of the patients receiving OAT in a TB hospital were retained for 12-months, either due to extraordinary high mortality in HIV/TB co-infected patients or inability to transfer patients to alternative OAT sites (Morozova et al, 2013). …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Irrespective of etiology, the healthcare reform should shift to more integrated care settings (Bachireddy et al, 2014; Sylla, Bruce, Kamarulzaman, & Altice, 2007) that incorporate treatment for HIV, TB and opioid dependence, including in hospitalized settings. Important in our findings is that none of the patients receiving OAT in a TB hospital were retained for 12-months, either due to extraordinary high mortality in HIV/TB co-infected patients or inability to transfer patients to alternative OAT sites (Morozova et al, 2013). …”
Section: Discussionmentioning
confidence: 95%
“…Explanations for this finding might include that Ukrainian guidelines requires inpatient hospitalization for all TB patients initially and involuntary discharge from OAT because TB hospitals may not provide onsite OAT. Alternatively, drop-out may be higher in TB patients due to high levels of MDR-TB and death in these patients (Morozova, Dvoryak, & Altice, 2013). Irrespective of etiology, the healthcare reform should shift to more integrated care settings (Bachireddy et al, 2014; Sylla, Bruce, Kamarulzaman, & Altice, 2007) that incorporate treatment for HIV, TB and opioid dependence, including in hospitalized settings.…”
Section: Discussionmentioning
confidence: 99%
“…Measures should be taken to help IDU patients to remain in care and overcome structural barriers, improve health literacy, and minimize stigma. There is a need for a patient-centred integrated multidisciplinary approach, involving both HIV and TB clinicians, as well as social support and provision of opiate substitution therapy, which is currently poorly available [28–31]. Integration of HIV and TB services, although improving, is still suboptimal in Eastern Europe and close collaboration of physicians from both specialities is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study found that OST alone was sufficient in improving the health related quality of life for HIV positive PWID (Bachireddy et al, 2013). Additionally, integration of methadone at inpatient TB facilities in Ukraine has also demonstrated favourable outcomes with respect to TB treatment retention and adherence (Morozova, Dvoryak, & Altice, 2013). …”
Section: Discussionmentioning
confidence: 99%